Effect of added polymer on the desiccation and healing of a geosynthetic clay liner subject to thermal gradients. Issue 6 (December 2020) - Yu, Bowei; El-Zein, Abbas; Rowe, R. Kerry
Abstract: The desiccation and subsequent hydraulic conductivity of both a standard (GCL_A) and polymer-enhanced (GCL_B) Na-bentonite GCL hydrated from a well-graded sandy subsoil under 20 kPa, then subjected to a thermal gradient, and finally rehydrated and permeated with distilled water or 0.325 mol/L Na + synthetic brine are reported. With moderate temperature of 40 °C applied to the top of the liner, GCL_B experienced less cracking than GCL_A, but this advantage disappeared when temperatures increased. Both desiccated specimens of GCL_A and B showed significant self-healing when permeated with distilled water and their hydraulic conductivities quickly reduced to around 10 −11 m/s at 20 kPa upon rehydration. However, when GCL_B desiccated specimens were permeated with the synthetic brine, their hydraulic conductivities were found to be one to two orders of magnitude higher than corresponding values obtained with distilled water. On the other hand, GCL_A (with no polymer treatment) maintained its hydraulic conductivities at the same level obtained with distilled water. It is concluded that caution should be exercised in using polymer-bentonite in applications in which GCLs are subjected to significant thermal gradients unless there is data to show they are resistant to thermal effects.